Value and Health Care Policy Ramifications of Rotator Cuff Repair. Issue 2 (June 2016) - Srikumaran, Uma; Hannan, Casey; Higgins, Laurence D.; Warner, Jon J.P.
Abstract : The societal burden of rotator cuff disease continues to increase with the aging of our population. Rotator cuff repairs have also become increasingly common over the last 2 decades. In our current cost conscious health care environment it is imperative to understand the value delivered to patients by various interventions. Value is most often equated with outcomes relative to the costs associated with care. To determine the value of different interventions, a thorough understanding of how to measure and interpret patient outcomes is crucial. In addition, calculating costs can be complex and physicians are often unaware of the costs related to their own decisions. Despite the complexities of measuring value, its benefits include heightened transparency in health care delivery, aligning stakeholders, and avoiding the trap of focussing solely on cost reductions, which may endanger effective treatment modalities.